Comparative effect of Aspartame and Sodium Cyclamate on Lipid Profile, Histology and Biochemical Parameters of Kidney and Liver Function in Albino Rats - Usman, Jiddah Nafiu; Abubakar, Salisu Maiwada; Gadanya, Aisha Muhammad (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Aspartame and Sodium cyclamate are two synthetic sweeteners used extensively in developing world. The study aims to assess the comparative effect of these sweeteners on lipid profiles, biochemical parameters of liver and kidney function and histological changes. Twenty male albino rats were separated into 5 groups of 4 rats each. Group 1 were fed normal diet and water, whereas those in Groups 2, 3, 4, and 5 received 50 mg/kg sodium cyclamate, 500 mg/kg sodium cyclamate, 50 mg/kg aspartame, and 500 mg/kg aspartame, respectively. After 7 weeks, the animals were sacrificed; blood and tissue samples were taken to analyze lipid profiles, biochemical parameters, and histology. The results showed that rats administered with low and high doses of sweeteners had significant (P<0.05) increase in serum triglyceride (TG) (0.92±0.05 mg/dL to 1.95±0.04 mg/dL), total cholesterol (TC) (4.88±0.31mg/dL to 8.18±0.45 mg/dL), low density lipoprotein (LDL) (3.59±0.26 mg/dL to 8.02±0.25 mg/dL), high density lipoprotein (HDL) (0.76±0.05 mg/dL to 1.11±0.1 mg/dL), Creatinine (0.94±0.08 mg/dL to 1.77±0.04 mg/dL) and urea (42.35±2.43 mg/dL to 57.3±1.79 mg/dL) levels in the treated group compared to the control group. Significant increase (P<0.05) in AST (47.33±3.92 U/L to 158.01±5.07 U/L), ALP (76.80±8.58 U/L to 124.01±1.51 U/L) and ALT (12.87±2.64 U/L to 37.74±5.76 U/L) levels was also observed in experimental group compared to the control group. Moreover, high doses of sweeteners caused more histological abnormalities in rats. Sodium cyclamate and aspartame maybe harmful to kidney and liver especially when consumed at high dose for a long period.